Long-term outcomes of latissimus dorsi flap breast reconstructions: A single-centre observational cohort study with up to 12 years of follow up. Issue 9 (September 2021) - Wattoo, G.; Nayak, S.; Khan, S.; Morgan, J.; Hocking, H.; MacInnes, E.; Kolar, K.M.; Rogers, C.; Olubowale, O.; Rigby, K.; Kazzazi, N.H.; Wyld, L.
Summary: Introduction: The Latissimus Dorsi Myocutaneous Flap (LDMF) is used in post-mastectomy reconstruction. This study has evaluated long-term (up to 12 years) surgical- and patient-reported outcomes from LDMF procedures. Method: A retrospective analysis of consecutive LDMF procedures in two UK hospitals, performed between 2006 and 2016. Case notes were reviewed for indications and outcomes. Patients were sent the BREAST-Q Ⓡ survey by post. Outcomes, including surgical adverse events, revision, and implant loss rates, were correlated with patient risk factors. Results: A BREAST-Q was posted to 199/248 LDMF patients in 2018, (excluding 49 patients due to death, reduced cognitive function and incorrect coding) of whom 77 patients responded (38.7%). In 188 cases (representing 208 LDMFs), surgical outcomes were assessable. Median time since LDMF surgery was 7 years (range 2–12). Rates of acute implant loss were 9/139 (6.4%), flap necrosis 7/208 (3.4%), shoulder stiffness 4/208 (1.9%), chronic pain 24/208 (11.5%) and unplanned revision surgery 13/208 (7%). Median satisfaction levels were high with 78% of patients satisfied with treatment outcomes, 65% of patients satisfied with their breasts, 71% of patients satisfied psychosocially and 75% of patients satisfied with their chest. Receipt of radiotherapy was not associated with a higher risk of flap necrosis or capsule formation. Conclusion: Long-term follow-up of a large cohort of LDMF reconstruction patients show relatively low levels of adverse events and unplanned revision surgery and high patient satisfaction, which demonstrates how temporally robust the technique is. With the rise in popularity of acellular dermal matrix reconstructions, the LDMF has relatively fallen out of favour but its potential in primary and delayed reconstruction is demonstrated.